2020
DOI: 10.1074/jbc.ra120.015929
|View full text |Cite
|
Sign up to set email alerts
|

A heterologous in-cell assay for investigating intermicrovillar adhesion complex interactions reveals a novel protrusion length-matching mechanism

Abstract: Solute transporting epithelial cells build arrays of microvilli on their apical surface to increase membrane scaffolding capacity and enhance function potential. In epithelial tissues such as the kidney and gut, microvilli are length-matched and assembled into tightly packed ‘brush borders’, which are organized by ~50 nm thread-like links that form between the distal tips of adjacent protrusions. Composed of protocadherins CDHR2 and CDHR5, adhesion links are stabilized at the tips by a cytoplasmic tripartite m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…ANKS4B is essential for the formation of the tip link complex and for the clustering of brush border microvilli. MYO7B, related to the MYO7A protein in stereocilia, anchors the complex to the actin core and likely transports the components to the microvillar tips (Weck et al, 2016, 2020). Calmodulin‐like protein 4 (CALML4) acts as the myosin light chain for MYO7B in the brush border (Choi et al, 2020).…”
Section: Intermicrovillar Protein Linksmentioning
confidence: 99%
“…ANKS4B is essential for the formation of the tip link complex and for the clustering of brush border microvilli. MYO7B, related to the MYO7A protein in stereocilia, anchors the complex to the actin core and likely transports the components to the microvillar tips (Weck et al, 2016, 2020). Calmodulin‐like protein 4 (CALML4) acts as the myosin light chain for MYO7B in the brush border (Choi et al, 2020).…”
Section: Intermicrovillar Protein Linksmentioning
confidence: 99%
“…Movement of MYO7B towards the tip of a microvillus has been observed and loss of motor activity eliminates the formation of connections between microvillar tips, resulting in the disorganization of microvilli 74 . An in vivo 'pull-down' strategy showed that ANKS4B, USH1C and the cytoplasmic domains of either CDHR2 or CDHR5 can bind to the MYO7B tail independently, suggesting that MYO7B could transport these components individually to the tip 81 . The exact nature of the cargo that MYO7B transports to the microvillar tip -a subset of components or all of them -is not known.…”
Section: Myosins and Microvillimentioning
confidence: 99%
“…Interestingly, filopodia tips enriched in CDHR2 and the chimeric motor appear to be gathered together, with several of them being matched in height. Occasionally, one filopodia tip can be observed to slide along the side of another filopodium until it reaches that tip and stops growing 81 . While this heterologous system is obviously lacking the normal actin regulators that build microvilli, these intriguing findings implicate the tension generated from two tips being linked together as another potential player in precisely controlling and matching the height of adjacent microvilli.…”
Section: Regulation Of Microvillar Lengthmentioning
confidence: 99%
“…scRNA-seq results confirm previous findings and correlate with the less studied CLDN8 in UC. UC-affected CTC cells also lose expression of CDHR5, an important intermicrovillar adhesion molecule that forms calcium-dependent heterophilic complexes with CDHR2 on adjacent microvilli ( 53 ). These two proteins control the packing of microvilli at the apical membrane of colonocytes and play a central role in brush border differentiation.…”
Section: Colonocytesmentioning
confidence: 99%